Computational Study of Mechanisms and Tether Length Effects of Rh‐Catalyzed [3+2] and [3+2+1] Reactions of Ene/Yne‐Vinylcyclopropanes. Issue 7 (22nd February 2023) - Zhang, Guan‐Yu; Lin, Mu; Yu, Zhi‐Xiang
Abstract: DFT calculations have been applied to study the mechanisms of [3+2] and [3+2+1] reactions of ene/yne‐vinylcyclopropanes (shorted as ene/yne‐VCPs). The [3+2] reactions of ene/yne‐VCPs start from C−C cleavage of cyclopropane (CP cleavage) to form six‐membered rhodacycle, followed by alkene/alkyne insertion and reductive elimination. The [3+2+1] reactions have two competing pathways, one is the [3+2+1] pathway (CP cleavage, ene/yne insertion, CO insertion and reductive elimination) and the other is the [3+1+2] pathway (CP cleavage, CO insertion, ene/yne insertion and reductive elimination). The length of tether in substrates affects the ene/yne insertion steps in these cycloadditions, making some reactions fail or changing the reaction pathways. The reasons for these tether length effects are discussed. Abstract : The mechanisms of [3+2] and [3+2+1] reactions using ene/yne‐vinylcyclopropanes have been studied computationally, finding that the length of tether affects the ene/yne insertion into Rh−C bond of the formed rhodacycles (from the cyclopropane cleavage), which in turn determines the reaction destinies and reaction pathways.